2001
DOI: 10.1051/animres:2001110
|View full text |Cite
|
Sign up to set email alerts
|

Grass valorisation and muscular characteristics of blonde d'Aquitaine steers

Abstract: -The blonde d'Aquitaine breed, the males of which are traditionally raised as young steers in intensive systems, is spreading beyond its region of origin. In pasture regions these males could be introduced into more extensive grazing systems. The purpose of this study is to assess the capability of these animals to valorise forage resources and also the characteristics of the carcasses produced and of the muscles concerned when considering meat tenderness. The study used young weaned bulls reared as beef anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
4
15
0
5
Order By: Relevance
“…CSA rises significantly (p \ 0.05) from 1,484 to 3,628 lm 2 for the LT and from 1,717 to 4,263 lm 2 for the ST. These results are fully consistent with those we obtained in 33-month-old bulls of the same breed (Listrat et al 2001). The relative expressions of the MyHC isoforms obtained with the electrophoresis method are compared to those obtained with the histological method (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…CSA rises significantly (p \ 0.05) from 1,484 to 3,628 lm 2 for the LT and from 1,717 to 4,263 lm 2 for the ST. These results are fully consistent with those we obtained in 33-month-old bulls of the same breed (Listrat et al 2001). The relative expressions of the MyHC isoforms obtained with the electrophoresis method are compared to those obtained with the histological method (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The same results were observed in DM muscles, from foetal to adult; DM muscles contain a higher proportion of fast glycolytic fibres (Gagnière et al, 1997Deveaux et al, 2001). Similar characteristics have also been observed in Blonde d'Aquitaine steers with enlarged muscle mass, as compared with Charolais steers (Listrat et al, 2001). These results are in accordance with those of Soike and Bergmann (1998) obtained in chicken bred for meat compared to egg production.…”
Section: Relationship Between Muscle Growth and Propertiessupporting
confidence: 87%
“…In this sense, in spite of the absence of significant differences in slaughter weight, Limousin carcass provided a higher percentage of First category cuts than Brown Swiss, and in general, higher amounts of saleable meat, and for this reason Limousin breed could be more advantageous for steer production. Our results are supported by a study of Listrat et al (2001) in Charolais and Blonde d'Aquitaine steers slaughtered at 33 months. These authors reported that Blonde d'Aquitaine showed a higher yield for carcass and muscle than Charolais steers without significant differences in slaughter weight.…”
Section: Discussionsupporting
confidence: 87%